Happy Valentine's Day, Charlie Brown! - Schulz, Charles M. (Charles Monroe), 1922-2000; Testa, Maggie (Ready-to-read. Superstar reader!, 2015)
As Valentine's Day approaches Charlie Brown tries to find the courage to give the Little Red-haired Girl a valentine.